An appraisal of local curriculum materials in social studies prepared in certain public elementary schools in Cagayan - Donato, Pilar (Manuel) 1918- (1956)
Determination of the effectiveness of the move to decentralize curriculum making through an appraisal of locally designed curricula in social studies prepared in the communities in Cagayan was the problem presented in this study. The study was subdivided into: the determination of the adequacy of the major parts of the locally prepared guides in social studies for grade four in enhancing the acquisition of knowledge, abilities and skills and the development of appreciation and democratic attitudes, and the comparison between the locally prepared guides with the Bureau of Public Schools guide in enhancing the goals of social studies.